2006
DOI: 10.1002/mawe.200600086
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for reliable durability validation of train axles

Abstract: Die Betriebsfestigkeit von Radsatzwellen hängt sowohl von der Betriebsbelastung als auch der Schwingfestigkeit ab. Zur Bewertung einer Radsatzwellen-Ausführung müssen die zeitlich veränderlichen Betriebsbeanspruchungen in einzelnen kritischen Bereichen, dargestellt durch die Beanspruchungskollektive, berücksichtigt werden. Die zulässige Beanspruchung in einzelnen Bereichen der Welle hängt sowohl von der örtlichen Ermüdungsfestigkeit als auch dem Beanspruchungskollektiv ab. Die Methodik zur Betriebsfestigkeitsb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 5 publications
2
38
0
Order By: Relevance
“…A first approach to optimize design can be to overcome the simple assessment in current standards [1][2], is to carry out an assessment based on fatigue damage calculations based on the fatigue damage calculated according to the , relative Miner rule' [12].…”
Section: Design According To Classical Fatigue Damage Calculationmentioning
confidence: 99%
“…A first approach to optimize design can be to overcome the simple assessment in current standards [1][2], is to carry out an assessment based on fatigue damage calculations based on the fatigue damage calculated according to the , relative Miner rule' [12].…”
Section: Design According To Classical Fatigue Damage Calculationmentioning
confidence: 99%
“…For chassis components, such as for example wheels, wheel-hubs, stub-axles or steering-rods, it must be assured that the required service life will not be reduced by rare special event loadings occurring from 10 up to 1000 times 1 Fraunhofer-Institute for Structural Durability and System Reliability LBF, Darmstadt/Germany 2 MAN Nutzfahrzeuge AG, Munich/Germany within the life cycle, possibly causing local remaining deformation below the structural yield point. Furthermore, it must be assured that, prior to a fracture caused by accident-like events, an energy release by local plastic deformation occurs, changing the failure location within the component but not yet causing total failure; this prevents serious aftermath of accidents [2].…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of these issues jointly results in a structural durability design of the components. Structural components can be identified as primary or secondary components, depending on how strongly they are related to safety and function of the vehicle [1]. Generally, safety components belong to the primary structural component category; their failure endangers the life of the user and other lives in the immediate surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1860, Wohler [3] proposed the validation of structures based on fatigue strength and indicated that residual stress contributed to the fracture of train axles. During operation, the working stress superimposed on internal residual stress reduces the margin of safety within the material.…”
Section: Introductionmentioning
confidence: 99%